OPTIMIZATION STRATEGY FOR SOLID TOXIC AND HAZARDOUS WASTE MANAGEMENT DURING THE COVID-19 PANDEMIC - Suci Adinda Rahmadia; Sri Wahyuni; Dolly Priatna (Journal of Science Innovare, 2022)
The increase in the number of hospitals in Indonesia has resulted in an increase in medical waste. Hospital activities have resulted in an increase in B3 waste which manages various problems. This research focuses on finding solutions and strategies in the framework of optimizing solid medical waste (B3) management. In particular, the optimization of medical waste management (B3) services involves several special analyzes, namely: priority needs, opportunities and constraints, and innovative work formulation programs. This study utilizes the Interpreted Structural Model (ISM) method to generate a priority scale in the management of solid B3 waste. This study found an analysis of the priority needs of mass education for all employees regarding the handling of solid B3 waste. Analysis of opportunities to increase stakeholder awareness of the dangers of B3 waste. The priority for solving the problem is that the organizational staffing is not complete according to the job description.